The Structural Pattern Of The Interrogative Sentence Between The Original And Its Abandonment/ النمط التركيبي لجملة الاستفهام بين الأصل والعدول عنه - Almalki, Mohammed Abdullah (Ijaz Arabi Journal of Arabic Learning, 2025)
The research aims to reveal the structural pattern of the interrogative sentence in the Arabic language, its characteristics compatible with the origin of linguistic use, and the manifestations of its transformation into other patterns that contradict that origin and are grammatically permissible. Because the large number of permissible grammatical images leads to difficulty for learners in understanding them, he relied on the descriptive doctrine based on collecting the statements of grammarians in describing the structure of the interrogative sentence and restricting the grammatical rulings to how the sentence is constructed. He collected data from Arabic grammar books across different eras, describing interrogative forms with examples. The research clarified the components of the interrogative sentence, the way they are arranged in the sentence, and the associated grammatical provisions that impact the form of the spoken or written sentence, whether related to deletion or separation of the components of the sentence or otherwise. The research aims to provide grammatically acceptable images of the interrogative sentence in a concentrated form in one template for the language learner to benefit from while speaking or writing and to understand what he reads or hears.